Diastereoselective synthesis of chiral 2,3-disubstituted lndolines via formal [3+2]-cycloaddition of arynes with gamma-amino-alpha,beta-unsaturated esters - Aher, Ravindra D.; Suryavanshi, Gurunath M.; Sudalai, Arumugam (Journal of Organic Chemistry, 2017)
A one step formal [3+2]-annulation protocol for the synthesis of 2,3-disubstituted indolines is described. The in situ generated aryne acts as a two-atom component, and gamma-amino-alpha,beta-unsaturated esters acting as a three-atom component to construct indoline units in a highly regio- and diastereoselective manner with yields ranging from 63 to 80%.